The Feejee Mermaid and Other Essays in Natural and Unnatural History - Bondeson, Jan (Book collections on Project MUSE., 2014)
In his new collection of essays, Jan Bondeson tells ten fascinating stories of myths and hoaxes, beliefs and Ripley-like facts, concerning the animal kingdom.